*O texto em movimento - Pugas Panichi, Edina Regina (Íkala, Revista de Lenguaje y Cultura, 2002)
This article aims to present partial results of the Research Project: "The Process of Text Elaboration in a Linguistic - Stylistic perspective from the analysis of the Literary Manuscript", carried on in the State University of Londrina. Working with the documents of the process, that is, the material registers used by the memorialist Pedro Nava to compose the volume Beira-Mar/Memórias 4, we followed trying to get close to his creative process through the footsteps he left. Our focus of attention is the process responsible for the generation of the work. With the support of the Genetic Criticism, we used the path of creation to deconstruct it and, afterwards, put it in action again. We analysed the purpose of the choices of resources by the author and the effects stemming from its application in his writing, as well the modifications the anotations suffer when they enter the universe of literary composition. Received: 06-06-02 / Accepted: 24-06-0 How to reference this article: Pugas Panichi, E. R. (2002). O texto em movimento. 7(1). Íkala. 7(1), pp. 17 – 26